Working capital management and corporate performance: Evidence from Sri Lankan listed manufacturing firms. - Vijayakumaran, R.; Vijayakumaran, S. (International Journal of Accounting and Financial Reporting,, 2017)
Working capital that represents a significant portion of a firm's total assets affects its profitability and liquidity. This study examines the performance effects of working capital management using a panel of listed manufacturing companies on the Colombo Stock Exchange (CSE) over the period 2011 to 2016. Controlling for unobservable firm specific heterogeneity and a set of observable firm characteristics, we document that working capital i s non-I i nearly (inverted U-shaped) related to firm prof itabi I ity. This indicates the existence of an optimal level of working capital that balances the costs and benefits of maintaining working capital, and maximizes firm's performance.
Keywords: Working capital management; Cash conversion cycle